Streptococcus sanguinis as an opportunistic bacteria in human oral cavity: Adherence, colonization, and invasion - Pramesti, Hening Tjaturina (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2016)
Streptococcus sanguinis (formerly S. sanguis) is a Gram-positive, facultative anaerobe,Â nonmotile , normalÂ inhabitant of the human oral cavity, andÂ a member ofÂ the viridans group of streptococci. Among the streptococcus, S. sanguinis is aÂ primary colonizer in the human tooth surface or it is recognize as a âpioneerâ by forming dental plaque. The aim of this paper is to review the role of Streptococcus sanguinisÂ in the adherence to andÂ invasion ofÂ human tissues.Â S. sanguinisÂ has been reportedÂ that it is associatedÂ with healthyÂ toothÂ surfacesÂ but not with caries. S. sanguinisÂ tend to involved in an interspecies interactions with Streptococcus mutans, which is known asÂ competition/coexistence within dental biofilm.Â In their colonization, this bacteria used enzyme sortase A (SrtA) to cleaveÂ LPXTG-containing proteins sequence andÂ anchoredÂ theÂ cell wall, while virulence factorsÂ in infective endocarditisÂ involved housekeeping functions such as cell wall synthesis, amino acid and nucleic acid synthesis, and the ability to survive under anaerobic conditions.